الطبيعة مصدر إلهام واستعارة في عملية التجسيد المعماري " تأثيرات الطبيعة على العملية التصميمية " - قصاب, أحمد سعيد; بدر, رنا; خلاص, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
تعد الفكرة التصميمية أحد أهم العناصر الأساسية خلال عملية التصميم، لطالما كانت الطبيعة عبر التاريخ مصدر إلهام للبداية البشرية في جوانب مختلفة من حياتها. لذلك لا يمكن تجسيد الهندسة المعمارية كواحدة من الميزات الرائعة في كل مجتمع للتعامل بمعزل عن الطبيعة الحاضنة. يقوم المهندسون المعماريون في الوقت الحالي ببناء المباني دونما اعتبار لدور الطبيعة كمستقبل لإرهاصاتهم الفكرية و تكويناتهم الحجمية مما يقلل من قيمة هذه المباني, ناهيك عن المحاولات العقيمة و بشكل كبير للاستفادة من هذه البيعة عبر استعارتها أو بعضا من أجزائها في الوظيفة – الشكل – الهيكل – الفلسفة المعمارية , لذلك يمكن القول أن النظر إلى الطبيعة في كل جانب أفضل حل للمهندسين المعماريين والمصممين لزيادة تحسين أعمالهم في التصميم عبر محاولة تطبيقها في تصميماتهم لمشاريعهم الذي هو قلب عملية التصميم في حين أن المهندسين المعماريين الآخرين قد أهملوا مفاهيم الطبيعة على الرغم من أن البيئة المحيطة والطبيعة تؤثر دائما على الإدراك البشري . Concept is on the most important and primary elements during the design process. Through the history, nature has been always a source of inspiration for the human begin in different aspects of their life. Architecture as one of the remarkable features in every society cannot be separated from nature. Nowadays architects and interior designers are constructing buildings without having a specific target or goal, which decreases the value of the buildings. Various designers have been using concepts inspired from nature but still there are some missing parts in one of their forms, function, or structure. Therefore, the best solution for the architects and designers to increase the optimization in their design works is looking at the nature in every aspect deeper and try to apply them in their conceptual design of their project which is the heart of the design process while other architects have neglected concepts of nature despite that the surrounding environment and nature always influences human perception. The aim of this research is to understand the relationship between nature and human perception and the role that nature plays in architectural interiors to achieve buildings integrated with the surrounding environment.